Biodiversity of the aculeate wasps (Hymenoptera: Aculeata) of the Arabian Peninsula: Preface - Gadallah, Neveen S.; Brothers, Denis J. (Zootaxa, 2020)
During the past 20 decades, many taxonomic and ecological studies were undertaken on different taxa of a fascinating, biologically diverse group of insects, the aculeate wasps, in different areas of the Arabian Peninsula. These wasps comprise all Aculeata, except for the ants (Formicidae) and bees (Anthophila) which are specialized monophyletic groups that have attracted more focused attention across the world. The Arabian studies have been published in the form of scattered articles in various journals, newsletters, book chapters, etc., many being rather obscure and difficult to trace. Recently, the number of such studies has increased as a result of targeted collecting projects. The results of most of these have now been published, making this an opportune time to collect all the available information into a single volume that makes it more accessible to researchers interested in this group of insects. In the process, this provides us an opportunity to estimate the diversity and distributions of aculeate wasps in the Arabian countries. This is also important for the development of the Arabian national collections, especially in aggregating taxonomic changes with their subsequent synonymous forms and pointing out the very many gaps in sampling, so indicating where additional work is needed.